Making Growth Work for the Poor : A Poverty Assessment for the Philippines - World Bank (World Bank, Manila, 2018)
The report emphasizes the importance of breaking the cycle of inequitable investment in human capital and lack of well-paying job opportunities that trap the poor in poverty, generation after generation. Children from poor households start life at a disadvantage. Malnourished and stunted, with poor access to quality health care, they are less likely to learn the skills they need and fulfill their potential. As adults, therefore, they earn low incomes and cannot afford to invest in their own children. They have little to meet their basic needs and nothing to save against emergencies. Frequent natural disasters buffet the poor, whose limited means to cope and disproportionate suffering push them deeper into poverty. Poverty is a threat to peace. In the parts of the country affected by conflict, where physical assets have been destroyed, families displaced, and human capital eroded, people are trapped in a cycle of conflict and poverty. In addition to the challenges of addressing poverty, the Philippines is hindered by the limited expansion of its middle class. In the East Asia region over 2002-2015, the share of population that is economically secure and middle class increased from just over one fifth to nearly two-thirds, but the share in the Philippines increased from 37 percent to just 44 percent. The lack of well-paying jobs limited the gains for labor from structural transformation. Every year, 1 percent of the employment shifted out of agriculture, but most of those workers end up in low-end services jobs. Such limited gains for labor could negatively affect the country’s long-term competitiveness. The report concludes that making the pattern of growth more inclusive and providing more well-paying jobs will be crucial to helping people achieve higher and more stable incomes. It claims that steps to accelerate poverty reduction include creating more well-paying jobs; improving productivity in all sectors, including agriculture; reducing income and wealth inequality through more investments in people and skills development, enhancing the ability of the poor to participate in growth; rebuilding conflict-affected areas; and better management of risks and protection of the vulnerable.